Electrochemical Dna Biosensor Based on Mercaptopropionic Acid-capped Zns Quantum Dots for Determination of the Gender of Arowana Fish - Eka Safitri; Lee Yook Heng; Musa Ahmad; Ling Ling Tan; Nazaruddin Nazaruddin; Khairi Suhud; Chew Poh Chiang; Muhammad Iqhrammullah (MDPI, 2024)
Indexed by WOS/Scopus/ERA